Diversity of Serotype, Genotype, and Antibiotic Susceptibility of Salmonella Prevalent in Pickled Ready-to-Eat Meat - Wang, Jiawei; Sheng, Huanjing; Xu, Weili; Huang, Jinling; Meng, Lingyuan; Cao, Chenyang; Zeng, Jie; Meng, Jianghong; Yang, Baowei (Frontiers in Microbiology, 2019)
Pickled ready-to-eat meat (PRTEM) is a meat product that is treated with various seasonings and then cooked. PRTEM is a popular food consumed mostly in China and some Asian countries. Since this food is considered ‘ready to eat’, once it is contaminated by foodborne pathogens such as Salmonella, the prospect for significant morbidity, mortality, and immeasurable economic losses can occur. Here we investigated the prevalence and concentration of Salmonella in 107 PRTEM samples collected from Shaanxi, China during 2015–2016. Furthermore, we analyzed the serotype, antibiotic susceptibility, and presence of antibiotic resistance genes and amino acid mutations in 219 Salmonella isolates, followed by subtyping of 115 representative isolates. The average detection rate of Salmonella-positive PRTEM was 58.9%, and the average most probable number (MPN) of Salmonella in positive samples was 2.27 logMPN per gram of sample (range: 2.10–2.43). Ten serotypes were identified from the 219 Salmonella isolates, with S. Thompson (37.9%) and S. Indiana (20.5%) being predominant. The remaining serotypes were S. Typhi (7.8%), S. Typhimurium (7.3%), S. Mbandaka (6.9%), S. Albany (6.4%), S. Blockley (5.5%), S. Infantis (4.1%), S. Escanaba (3.2%), and S. Dusseldorf (0.5%). All isolates were resistant to ceftiofur (100%), while most of them were resistant to ciprofloxacin (99.1%), amoxicillin-clavulanic acid (97.7%), trimethoprim-sulfamethoxazole (96.4%), ampicillin (92.3%), sulfisoxazole (92.2%), tetracyclines (90.4%), and nalidixic acid (90.4%), respectively. A single mutation of Ser83Phe (27.1%) and double mutations of Ser83Phe-Asp87Gly (25.9%) in GyrA were detected in 85 isolates, whereas mutations of Thr57Ser (63.9%) and Ser80Arg (36.1%) in ParC were detected in 122 isolates. qnrB, oqxAB, aac(6’)-Ib, and qnrA were present in 50 (22.8%), 48 (21.9%), 26 (11.9%), and 1 (0.5%) isolate(s), respectively. Pulse field gel electrophoresis results revealed that those isolates recovered from the same type of PRTEM or the same sampling place shared identical or similar DNA profiles, antibiotic resistance phenotypes, and even plasmid-mediated quinolone resistance encoding genes. The ﬁndings indicate that Salmonella is commonly prevalent in PRTEMs at high concentrations in Shaanxi, China. More attention should be paid to the processing and storage of this ready-to-eat food to prevent bacterial contamination and foodborne outbreaks.